Implementasi Penanganan Benturan Kepentingan di Lingkungan Komisi Pemilihan Umum Kota Palembang - Purnamawati, Evi (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Handling conflicts of interest is a crucial aspect in conducting elections with integrity. The General Election Commission (KPU) as the election organizer is required to maintain independence, neutrality, and professionalism. This study aims to analyze the implementation of conflict of interest management within the General Election Commission (KPU) of Palembang City, the inhibiting factors, and improvement strategies. The research method uses a qualitative approach with normative descriptive analysis and field studies through in-depth interviews with commissioners and secretariat staff of the General Election Commission (KPU) of Palembang City. The results show that although regulations on conflicts of interest are available through the General Election Commission (KPU) Regulation and the State Civil Service Commission (KASN) Regulation, their implementation still faces obstacles, such as a lack of understanding among human resources, limited internal monitoring mechanisms, and the potential for local political intervention. Therefore, institutional strengthening strategies, ethics training for organizers, and transparent public reporting mechanisms are needed.